Oxytocin in growth, reproduction, restoration and health - Kerstin Uvnäs Moberg (Comprehensive Psychoneuroendocrinology)
This article summarizes my scientific work and describes some personal experiences during this period. After my basal medical training (MD) (1971), I obtained a PhD in pharmacology (1976) and ended up as a professor of Physiology.My initial studies were within the field of gastroenterology. I showed that the gastrointestinal hormone gastrin, which stimulates HCL secretion in the stomach, was released in response to stimulation of the vagal nerve. Later I showed that the entire endocrine system of the gastrointestinal (GI) tract that promotes digestion and anabolic metabolism and growth was under vagal nerve control. I also showed that activation of the vagal nerve inhibits the function of the inhibitory substance somatostatin.10 years later, after some big changes in my personal life, my research focus changed. I became interested in female physiology, particularly the role of oxytocin. In addition, I became aware of the situation of female scientists and started to work with questions regarding equality between women and men.I gathered a group of interested female medical students and midwives around me. We demonstrated that breastfeeding and touch (e.g., between mother and baby), via stimulation of sensory nerves in the skin, activated the endocrine system of the GI tract and, thereby, anabolic processes and growth. The effects were exerted via a vagal mechanism and involved activation of parvocellular oxytocinergic neurons from the paraventricular nucleus (PVN). We also showed that the gastrointestinal hormone cholecystokinin stimulated the release of oxytocin in a calorie-dependent way via an afferent vagal mechanism.In summary, there is a bidirectional, vagally mediated connection between the endocrine system of the GI tract and the oxytocin producing neurons in the supraoptic (SON) and paraventricular (PVN) nuclei of the hypothalamus.1. Oxytocinergic neurons from the PVN enhances the activity of the endocrine system of the GI tract and thereby growth and regeneration. The effect is exerted via efferent vagal fibers which inhibit the release of somatostatin. 2. Food in the duodenum triggers a release of cholecystokinin (CCK), which via a vagal afferent mechanism stimulates the release and function of oxytocin. This mechanism is not activated in the absence of food intake.Administration of oxytocin induces a multitude of actions, i.e., anxiolytic and sedative effects, increased pain threshold, lowering of cortisol and blood pressure and an increased activity of the endocrine system of the GI tract. Repeated administration of oxytocin may induce long-term effects and “secondary” mechanisms such as an increased activity of alpha-2- adrenoceptors are involved.Oxytocin released by suckling during breastfeeding or by touch during social interaction will induce a similar effect spectrum. Activation of the parvocellular neurons will stimulate some aspects of social behavior, induce calm and well-being, and decrease levels of fear, stress, and pain. In addition, vagal functions and the activity of the endocrine system of the GI tract will be stimulated. Together, these effects are consistent with the oxytocin-mediated calm and connection response and, in a long-term perspective, with the promotion of well-being and health.A second period of professional difficulties occurred in the late 1990s. I moved to the Swedish University of Agriculture, where I started to investigate the role of oxytocin in interactions between humans and pets, as this type of interaction had been shown to promote health. I continued to study the role of oxytocin in female reproduction, in particular, the role of oxytocin during labor and birth and in the peripartum period. In addition, I started to write books about different aspects of oxytocin.I also wanted to establish a role for oxytocin in the treatment of vaginal atrophy. Several clinical studies show that local intravaginal application of oxytocin in women with vaginal atrophy increases the regeneration of vaginal mucosal cells and function.